2021
DOI: 10.1007/s00705-021-05298-2
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian animal models for dengue virus infection: a recent overview

Abstract: Dengue, a rapidly spreading mosquito-borne human viral disease caused by dengue virus (DENV), is a public health concern in tropical and subtropical areas due to its expanding geographical range. DENV can cause a wide spectrum of illnesses in humans, ranging from asymptomatic infection or mild dengue fever (DF) to life-threatening dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Dengue is caused by four DENV serotypes; however, dengue pathogenesis is complex and poorly understood. Establishing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 141 publications
0
15
0
Order By: Relevance
“…Preexisting immunities play distinct roles in subsequent viral pathogenesis and even outcome. The studies conducted on different models always draw different conclusions: prior JEV immunity offered cross-protection against DENV in mice [38], while a contrary conclusion was obtained in the population study [50] but, as an acknowledged limitation, there is no ideal mouse model to investigate the ADE [63]. Therefore, no symptom or complete survival in the mouse model does not signify that sequential infections of flaviviruses are dependable for human beings [5].…”
Section: Model Effect Probable Mechanismmentioning
confidence: 99%
“…Preexisting immunities play distinct roles in subsequent viral pathogenesis and even outcome. The studies conducted on different models always draw different conclusions: prior JEV immunity offered cross-protection against DENV in mice [38], while a contrary conclusion was obtained in the population study [50] but, as an acknowledged limitation, there is no ideal mouse model to investigate the ADE [63]. Therefore, no symptom or complete survival in the mouse model does not signify that sequential infections of flaviviruses are dependable for human beings [5].…”
Section: Model Effect Probable Mechanismmentioning
confidence: 99%
“…We verified the role of vimentin in DENV invasion in SV129 suckling mice with and without vimentin knockout. Many models have been used to study DENV, including A/J ( Shresta et al., 2004 ), BALB/c ( Ahmad et al., 2019 ), C57BL/6 ( Byrne et al., 2020 ), and AG129 ( Tan et al., 2010 ) mice for dengue virus tropism and pathogenic research; the DENV-infected non-human primate ( Kayesh and Tsukiyama-Kohara, 2022 ), AG129 mouse continuous infection, cross-infection-established ADE mouse models to study the immune mechanisms of DENV infection ( Blaney et al., 2002 ); and DENV-infected suckling mouse ( Pelliccia et al., 2017 ) and DENV-infected SCID mouse models in vaccine research. In this study, we used suckling mice because adult mice displayed no obvious clinical signs after infection, and DENV-2 was not detected in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Papillomavirus infections have also been shown to alter the levels of these miRNAs in cells, having important effects on the p53 signaling pathway (22)(23)(24). Even though studies have shown that DENV is harmful (25,26), the molecular basis of apoptosis is not well understood. miRNA-15 is a lot like miRNA-16, which is also involved in apoptotic pathways and cell growth during oncogenic processes (25,27).…”
Section: Discussionmentioning
confidence: 99%